2021
DOI: 10.3389/fcell.2021.774370
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Among circRNA/lncRNA, miRNA, and mRNA in Osteoarthritis

Abstract: Osteoarthritis (OA) is a joint disease that is pervasive in life, and the incidence and mortality of OA are increasing, causing many adverse effects on people’s life. Therefore, it is very vital to identify new biomarkers and therapeutic targets in the clinical diagnosis and treatment of OA. ncRNA is a nonprotein-coding RNA that does not translate into proteins but participates in protein translation. At the RNA level, it can perform biological functions. Many studies have found that miRNA, lncRNA, and circRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 395 publications
0
31
0
Order By: Relevance
“…miRNA is a kind of small single-stranded RNA molecule encoded by endogenous genes, with a length of about 22 nucleotides. It is not translated into protein, but participates in the process of protein translation ( 74 ). miRNA has three main characteristics: time and space specificity, high selectivity and conservation of structure and sequence, which makes it an ideal biomarker for medical clinical diagnosis ( 75 ).…”
Section: Hmgs In Sepsismentioning
confidence: 99%
“…miRNA is a kind of small single-stranded RNA molecule encoded by endogenous genes, with a length of about 22 nucleotides. It is not translated into protein, but participates in the process of protein translation ( 74 ). miRNA has three main characteristics: time and space specificity, high selectivity and conservation of structure and sequence, which makes it an ideal biomarker for medical clinical diagnosis ( 75 ).…”
Section: Hmgs In Sepsismentioning
confidence: 99%
“…CRP, as a component of the innate immune system, during infection may recognize various pathogens associated molecular patterns (PAMPs) such as phospholipid fragments released from damaged cells consequently activating the complement system and finally inducing the death of the targeted cells [ 28 ]. CRP is released into the bloodstream after 4–6 h after an inflammatory stimulus and a plasma peak is reached in 36 to 50 h [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Several conditions besides infection can result in the elevation of the CRP-serum level [ 30 ]; a meta-analysis of Simon et al [ 31 ] demonstrated a sensitivity of 75% [95% CI: 62–84%] and a specificity of 67% [95% CI: 56–77%] for CRP in differentiating bacterial infection from the noninfective cause of inflammation.…”
Section: Role Of Biomarkers In Sepsismentioning
confidence: 99%
“…Further demonstrating the increasing biological value that non-coding RNAs are proving to have, they seem to play a role in the pathogenesis of different diseases [ 18 ], and, given the complex interweaving between circRNAs, miRNAs, lncRNAs and mRNAs, various studies have addressed the issue of their role as novel diagnostic markers and therapeutic targets in many pathologic conditions including sepsis [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the comprehensive understanding of mechanical response of chondrocyte transcriptome landscape, including mRNAs, microRNAs (miRNAs), lncRNAs, and circular RNAs (circRNAs), is still absent. The roles of noncoding RNAs (ncRNAs) in mechanotransduction remain elusive, while some ncRNAs were identified as the indispensable participators in OA pathogenesis ( Li et al, 2018 ; Malemud, 2018 ; Kong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%